REFLECTIVE SPIRITUAL LITERACY MODEL THROUGH PRAYER AND ASMAUL HUSNA HABITUATION FOR STRENGTHENING RELIGIOUS CHARACTER IN ELEMENTARY STUDENTS - Al Najwa, Syalaysa Fhenia; Robiansyah, Firman; Oki Suprianto (PIONIR: JURNAL PENDIDIKAN, 2026)
This study aims to develop and describe a reflective spiritual literacy model implemented through the habituation of reciting prayers and Asmaul Husna to strengthen elementary school students’ religious character. This research employed a qualitative approach with a case study design conducted at SDN Serang 20. Data were collected through in-depth interviews, observations, questionnaires, and documentation, and analyzed using an interactive model with triangulation techniques.The findings reveal that the implementation of reflective spiritual literacy transforms ritual religious activities into meaningful and reflective practices. Approximately 90% of student responses fall into the appropriate category, indicating improvements in spiritual awareness, worship habits, self control, and social religious attitudes. The model integrates three main stages: guided habituation, contextual meaning making, and structured reflection. These results demonstrate that reflective spiritual literacy is effective in fostering internalization of religious values and promoting sustainable character development. The study contributes an integrative model that shifts religious habituation from mechanical routines to reflective and transformative learning experiences. Keywords: Reflective Spiritual Literacy, Prayer Habituation, Asmaul Husna, Religious Character, Elementary School